2005
DOI: 10.1002/pmic.200401125
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of urine in patients with intestinal segments transposed into the urinary tract

Abstract: Intestinal segments are used to replace or reconstruct the urinary bladder when it has become dysfunctional or develops life-threatening disease such as cancer. The quality of life in patients with intestinal segments used to either enlarge or completely replace the native bladder is adversely affected by recurrent urinary tract infections, excessive mucus production and the occasional development of malignancy. At present, there is no reliable method of predicting or noninvasively monitoring these patients fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Two-dimensional electrophoresis (2-DE) of proteins has been the conventional method for biomarker assessment in urological proteomics (33, 34). Irmak et al identified two proteins, orosomucoid (ORM) and zinc-alpha glycoprotein (ZAG) which were increased in urine samples of tumor-bearing patients in comparison with samples from a few healthy volunteers (17), and Pinero et al used 2D-DIGE coupled with mass spectrometry to identify regenerating protein-1 (Reg-1) and keratin 10 as being associated with bladder cancer (35).…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional electrophoresis (2-DE) of proteins has been the conventional method for biomarker assessment in urological proteomics (33, 34). Irmak et al identified two proteins, orosomucoid (ORM) and zinc-alpha glycoprotein (ZAG) which were increased in urine samples of tumor-bearing patients in comparison with samples from a few healthy volunteers (17), and Pinero et al used 2D-DIGE coupled with mass spectrometry to identify regenerating protein-1 (Reg-1) and keratin 10 as being associated with bladder cancer (35).…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional electrophoresis (2-DE) of proteins has been the conventional method for biomarker assessment in urological proteomics, 14,15 and investigators have performed a systematic evaluation of sample preparation methods for gelbased human urinary proteomes. 16 A near-standard 2-D map 17 and high-resolution 2-D gels 18 of urological tissues have contributed to the construction of a 2-D database.…”
Section: Discussionmentioning
confidence: 99%
“…Nephrologists and urologists have begun to use mass spectrometry-based methods for discovery of potential disease biomarkers for a number of renal diseases including diabetic glomerulopathy (14,16,37,69), acute renal injury (22), IgA nephropathy (15), Fanconi syndrome of various causes (29,31,70), idiopathic glomerulopathy (13), congenital obstructive nephropathy (39,71), vesicoureteral reflux (72), interstitial cystitis (73), and urinary bladder reconstruction (74).…”
Section: Urinary Proteomics In Nephrology and Renal Transplantationmentioning
confidence: 99%